Pendampingan Projek Penguatan Profil Pelajar Pancasila di MAN 4 Banyuwangi - Atiqatul Musyarofah; Imam Mashuri; Fathi Hidayah; Al Muftiyah (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
The implementation of the Merdeka Curriculum requires educational institutions to be prepared in managing the Project for Strengthening the Profile of Pancasila Students (P5). However, in practice, many madrasahs still face obstacles in synchronizing project themes with local values and religious moderation. Objective: This study aims to describe the process and results of mentoring the implementation of P5 at MAN 4 Banyuwangi to improve the effectiveness of project-based learning. Methods: This mentoring activity utilized a qualitative descriptive approach, with data collection techniques including observation, interviews with project coordinators, and documentation of students' work. Results: The mentoring results indicated that effectiveness was achieved through fashion shows accompanied by dramas and intensive guidance. Furthermore, there was a significant improvement in student character dimensions, particularly in the habituation of implementing the values of struggle, cooperation, discipline, and nationalism in daily life. Conclusion: Structured mentoring has proven effective in accelerating the understanding of the madrasah's academic community in implementing P5 meaningfully.